2007
DOI: 10.1111/j.1574-6968.2006.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the structure ofSphingomonasspp. communities associated with biodegradation of the herbicide isoproturon in soil

Abstract: The phenyl-urea herbicide isoproturon is a major contaminant of surface and ground-water in agricultural catchments. Earlier work suggested that within-field spatial variation of isoproturon degradation rate resulted from interactions between catabolizing Sphingomonas spp. and pH. In the current study, changes to the structure of Sphingomonas communities during isoproturon catabolism were investigated using Sphingomonas-specific 16S rRNA gene primers. Growth-linked catabolism at high-pH (>7.5) sites was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…() suggested that intrinsic soil parameters (such as pH, available potassium or C total /N total ratio) affected the actively linuron‐metabolizing bacterial community in soil. Shi & Bending () observed the dominance of different Sphingomonas phylotypes that could be linked to isoproturon degradation at different locations in the examined agricultural field, as a result of differences in local pH values. In addition to spatial, temporal changes in soil microbial community structure/composition might be responsible for the observed differences in linuron‐degrading entities between the two experiments.…”
Section: Discussionmentioning
confidence: 99%
“…() suggested that intrinsic soil parameters (such as pH, available potassium or C total /N total ratio) affected the actively linuron‐metabolizing bacterial community in soil. Shi & Bending () observed the dominance of different Sphingomonas phylotypes that could be linked to isoproturon degradation at different locations in the examined agricultural field, as a result of differences in local pH values. In addition to spatial, temporal changes in soil microbial community structure/composition might be responsible for the observed differences in linuron‐degrading entities between the two experiments.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that a pure sphingomonad strain can yield multiple patterns targeting the 16S rRNA gene (14,26). Shi and Bending (26) speculated that this phenomenon was due to the possession of multiple 16S rRNA gene copies with sequence divergence in the genome of a sphingomonad.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingomonads were found to be ubiquitous in a variety of PAH-contaminated soils by employing a method of denaturing gradient gel electrophoresis (DGGE) exclusively targeting the sphingomonad community (14). Significant changes in sphingomonad communities involved in the degradation of the herbicide isoproturon were demonstrated by employing DGGE (26). An association of bacteria closely related to sphingomonads in the rhizospheres of wheat and maize was revealed using DNA arrays (8).…”
mentioning
confidence: 99%
“…하지만, 수생환경에 잔류하는 난분해 성 물질의 제거 및 분해에 대한 연구는 대부분 수생식물을 이 용한 화학물질 흡착 및 수생 생태 환경의 복원에 대한 연구이 다 (Liao and Chang, 2004;Jayaweera and Kasturiarachchi, 2004). 하지만 nonylphenol의 생물학적 분해에 관하여서는 국 외에서도 nonylphenol 분해 미생물의 분리에 대한 보고만 되 어있는 정도이며 국내에서는 이에 대한 연구가 아직 이루어 지고 있지 않다 (Tanghe et al, 1999;Fujii et al, 2000;Fujii et al, 2001;Corvini et al, 2004;Junghanns et al, 2005;Shi and Bending, 2007 Table 2).…”
Section: 서 론unclassified